Identification of immune and viral correlates of norovirus protective immunity through comparative study of intra-cluster norovirus strains. - Shu Zhu; Doron Regev; Makiko Watanabe; Danielle Hickman; Nissin Moussatche; Desyree Murta Jesus; Shannon M Kahan; Sawsan Napthine; Ian Brierley; Robert N Hunter; Divya Devabhaktuni; Melissa K Jones; et al. (PLoS Pathogens)
Whether or not primary norovirus infections induce protective immunity has become a controversial issue, potentially confounded by the comparison of data from genetically distinct norovirus strains. Early human volunteer studies performed with a norovirus-positive inoculum initially led to the conclusion that primary infection does not generate long-term, protective immunity. More recently though, the epidemiological pattern of norovirus pandemics has led to the extrapolation that primary norovirus infection induces herd immunity. While these are seemingly discordant observations, they may in fact reflect virus strain-, cluster-, or genogroup-specific differences in protective immunity induction. Here, we report that highly genetically related intra-cluster murine norovirus strains differ dramatically in their ability to induce a protective immune response: Primary MNV-3 infection induced robust and cross-reactive protection, whereas primary MNV-1 infection induced modest homotypic and no heterotypic protection. In addition to this fundamental observation that intra-cluster norovirus strains display remarkable differences in protective immunity induction, we report three additional important observations relevant to norovirus:host interactions. First, antibody and CD4⁺ T cells are essential to controlling secondary norovirus infections. Second, the viral minor structural protein VP2 regulates the maturation of antigen presenting cells and protective immunity induction in a virus strain-specific manner, pointing to a mechanism by which MNV-1 may prevent the stimulation of memory immune responses. Third, VF1-mediated regulation of cytokine induction also correlates with protective immunity induction. Thus, two highly genetically-related norovirus strains displayed striking differences in induction of protective immune responses, strongly suggesting that the interpretation of norovirus immunity and vaccine studies must consider potential virus strain-specific effects. Moreover, we have identified immune (antibody and CD4⁺ T cells) and viral (VP2 and possibly VF1) correlates of norovirus protective immunity. These findings have significant implications for our understanding of norovirus immunity during primary infections as well as the development of new norovirus vaccines.